2015
DOI: 10.1063/1.4919871
|View full text |Cite
|
Sign up to set email alerts
|

The fundamental downscaling limit of field effect transistors

Abstract: We predict that within next 15 years a fundamental down-scaling limit for CMOS technology and other Field-Effect Transistors (FETs) will be reached. Specifically, we show that at room temperatures all FETs, irrespective of their channel material, will start experiencing unacceptable level of thermally induced errors around 5-nm gate lengths. These findings were confirmed by performing quantum mechanical transport simulations for a variety of 6-, 5-, and 4-nm gate length Si devices, optimized to satisfy high-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 20 publications
(17 reference statements)
0
51
0
Order By: Relevance
“…The switching energy (energy dissipation per switching event) of a single CMOS gate is expected to reach 100 k B T , where k B is the Boltzmann's constant and T is temperature, by reducing the feature size to approximately 5 nm [1]. However, since 100 k B T switching energy is a thermal limit for normal (non-adiabatic) CMOS logic [1], [2], it is not practical to achieve even smaller switching energy via device miniaturization. One possible solution to go beyond this limit is to adopt reversible computing [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…The switching energy (energy dissipation per switching event) of a single CMOS gate is expected to reach 100 k B T , where k B is the Boltzmann's constant and T is temperature, by reducing the feature size to approximately 5 nm [1]. However, since 100 k B T switching energy is a thermal limit for normal (non-adiabatic) CMOS logic [1], [2], it is not practical to achieve even smaller switching energy via device miniaturization. One possible solution to go beyond this limit is to adopt reversible computing [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Unavoidable problems arise, such as heat dissipation and quantum effects, etc. [ 5 , 6 ] The channel materials are crucial to enable high-performance device designs. It was shown that 5-nm will be the limit of channel length in field effect transistors (FETs) based on Si [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 6 ] The channel materials are crucial to enable high-performance device designs. It was shown that 5-nm will be the limit of channel length in field effect transistors (FETs) based on Si [ 6 ]. Among the many possible candidates as suggested in the ITRS [ 4 ], 2D materials are the mostly likely to be used in next-generation transistors [ 7 , 8 ] due to their ultimate thickness providing excellent gate control and their dangle bond–free surfaces preventing additional inelastic electron scattering.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to consider the non zero probability of electrons tunneling through the energetically forbidden regions between the individual transistors. This makes the performance of the electronic device unreliable and unstable [14].…”
Section: Chapter 1 Introductionmentioning
confidence: 99%